Technical Efficiency Analysis of citrus properties from São Paulo - Clemente, Felippe; Gomes, Marília Fernandes Maciel; Lírio, Viviani Silva (Economia Aplicada, 2015)
This study aimed at analyzing the technical efficiency of citrus farms in the State of São Paulo.For that, data envelopment analysis was applied (DEA) to calculate the levels of technical efficiency, and an econometric approach was used to know the determinants of technical efficiency. The results showed that the majority of citrus properties of São Paulo operate inefficiently and the variables that contribute most to increasing efficiency are "schooling" and "time as farmers." The average production and frontier functions were different regarding the magnitude of its parameters, indicating that the instrumental analysis is very important and its correct estimation and interpretation, can facilitate decision making and significantly improve the allocation of resources.